2020
DOI: 10.1002/cey2.44
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress on MOF‐derived carbon materials for energy storage

Abstract: Metal‐organic frameworks (MOFs) are of quite a significance in the field of inorganic‐organic hybrid crystals. Especially, MOFs have attracted increasing attention in recent years due to their large specific surface area, desirable electrical conductivity, controllable porosity, tunable geometric structure, and excellent thermal/chemical stability. Some recent studies have shown that carbon materials prepared by MOFs as precursors can retain the privileged structure of MOFs, such as large specific surface area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
101
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(116 citation statements)
references
References 192 publications
(302 reference statements)
2
101
0
Order By: Relevance
“…With abundant metal/organic species and extraordinary tunability of structures, MOFs are promising self‐sacrificing templates/precursors for preparation of carbon‐based conductive nanomaterials by the calcination treatment. [ 170–178 ] Generally speaking, the MOFs‐derived conductive materials mainly include (heteroatom‐doped) porous carbons, metal‐based compounds, and their hybrids. [ 170,171 ] Benefit from the unique pore distribution and structure characteristics of MOF‐based precursors, the MOFs‐derived materials usually have the advantages of tailorable morphologies and hierarchical porosity.…”
Section: The Design and Synthesis Of Conductive Mofsmentioning
confidence: 99%
“…With abundant metal/organic species and extraordinary tunability of structures, MOFs are promising self‐sacrificing templates/precursors for preparation of carbon‐based conductive nanomaterials by the calcination treatment. [ 170–178 ] Generally speaking, the MOFs‐derived conductive materials mainly include (heteroatom‐doped) porous carbons, metal‐based compounds, and their hybrids. [ 170,171 ] Benefit from the unique pore distribution and structure characteristics of MOF‐based precursors, the MOFs‐derived materials usually have the advantages of tailorable morphologies and hierarchical porosity.…”
Section: The Design and Synthesis Of Conductive Mofsmentioning
confidence: 99%
“…At the same time, atmospheric oxygen diffuses into the porous air electrode and is reduced through the ORR to form OH − (Equation (1)). The OH − first binds Zn 2+ to form Zn(OH) 4 2− , and then further generates insoluble ZnO (Equation (2)) when Zn(OH) 4 2− reaches saturation in the electrolyte. The overall reaction for ZABs is presented as Equation 3, with an equilibrium cell voltage of 1.66 V. The air electrode consists of a substrate and a catalyst layer, providing the accommodation for both the ORR and OER.…”
Section: The Configuration Of Solid-state Zabsmentioning
confidence: 99%
“…[ 3 ] Therefore, highly efficient energy storage devices are required to enhance the energy efficiency and optimize the loading distribution of the electrical grid. [ 4 ] To date, Li‐ion batteries have become the most successful solution for energy conversion and storage, and they have been widely used in portable electronics and electric vehicles (EVs). [ 5 ] However, the long‐standing disadvantages of high cost, insufficient energy density, lithium scarcity, and safety concern significantly limit their large‐scale applications in the automobile industry, especially for the extended range EVs.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that several types of carbon hosts, including hollow carbon, [19] porous carbon, [20] disordered carbon nanotubes, [21] mesoporous carbon nanoparticles, [22] double-shelled hollow carbon spheres, [23] and carbon foam, [24] have made significant enhancement in delivering specific capacity and cycling stability of Li-S batteries. However, the preparation of these complicated carbon materials involves several complicated and energy-intensive steps, [25][26][27] increasing the thermal budget and carbon footprint. Therefore, to reduce the overall cost considerably, it is imperative to develop facile strategies to recycle the valuable carbon hosts at their end-of-life.…”
Section: Introductionmentioning
confidence: 99%